Lifestyles of university students in confinement by covid-19 - Prado Juscamaita, Justina Isabel; Gutarra Vara, José Bernardino; Blanco Aliaga, Milba (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This research analyzed the confinement due to covid-19 and the lifestyles of the students of the Faculty of Obstetrics of the Hermilio Valdizán National Universi- ty. We worked with a sample of 104 students, the technique used was the online survey with valid and reliable instruments. Results: 96% of the students reported having had a total confinement, 85.6% of the students have had healthy lifestyles. Finally, finding the p value of 0.039 less than 0.05, it is affirmed that the confine- ment due to covid-19 influences the lifestyles of the students.